1999
DOI: 10.1103/physrevb.59.r10449
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of sulfur dimers in alkanethiol self-assembled monolayers on Au(111)

Abstract: High-resolution electron-energy-loss spectra of octadecanethiol self-assembled monolayers ͑SAM's͒ on Au thin films have been obtained after annealing the sample to various temperatures. Annealing to 375 K results in the appearance of the S-S stretch at 530 cm Ϫ1 , a direct observation of sulfur dimers for alkanethiol SAM's adsorbed on Au. The appearance of dimers following annealing is explained by the presence of an activation barrier to the formation of gauche defects at the S-C bond. ͓S0163-1829͑99͒51016-3͔… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
126
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 28 publications
11
126
0
Order By: Relevance
“…Our calculation indicates that two intact methanethiol molecules do not form a dimer on the perfect Au(111) surface, which is consistent with the respective observation in Refs. [17], [24] and [25]. These findings resolve the controversial issue of bond cleavage at low or room temperature.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Our calculation indicates that two intact methanethiol molecules do not form a dimer on the perfect Au(111) surface, which is consistent with the respective observation in Refs. [17], [24] and [25]. These findings resolve the controversial issue of bond cleavage at low or room temperature.…”
supporting
confidence: 54%
“…The emergence of thiolate on the Au(111) surface reflects the presence of surface defects. Defects might be caused in the process of gold surface production, or temperature enhancement [24] or exposure to X-rays [27]. The sulfur dimers were proposed on the basis of X-ray diffraction (XRD) data obtained at saturated coverage [28], but we have found that a pair of intact methanethiols cannot form a dimer on the defectfree Au(111) surface.…”
mentioning
confidence: 99%
“…The major peak positions are in good agreement with those reported previously for incubated octadecanethiol/Au(111). 29 In contrast to the IRRAS spectra for 1,6 HDT, several modes are observed in the 1000-1500 cm -1 region and can be assigned to CH 2 bending modes and C-C stretch modes. The mode at 720 cm -1 can be assigned to the C-S stretch.…”
mentioning
confidence: 82%
“…From infrared data it was concluded that there are two different orientations in the alkyl chains [40] and from grazing incidence X-ray diffraction data, a model was proposed for the superstructure based upon thiolate dimers [41]. Evidence against the dimer model was presented by scanning tunneling microscopy [42] and by electron spectroscopy experiments [43]; in the latter, thiolate dimers were found only at temperatures above 375K. In recent He and X-ray diffraction experiments it was concluded that in the (4 2) c × superstructure alkyl-thiolate molecules adsorb as monomers on the Au(111) surface [44,45].…”
Section: Structuresmentioning
confidence: 99%